2003
DOI: 10.1614/wt02-157
|View full text |Cite
|
Sign up to set email alerts
|

Spray Volume, Formulation, Ammonium Sulfate, and Nozzle Effects on Glyphosate Efficacy1

Abstract: Field experiments were conducted to examine the influence of spray volume on glyphosate efficacy in relation to glyphosate rate, formulation, ammonium sulfate addition, and type of sprayer nozzle. Using several grass species it was shown that glyphosate efficacy increased as spray volume decreased from 190 to 23 L/ha. To obtain equal efficacy, glyphosate rates can be reduced by at least one-third when glyphosate is applied in 23 or 47 L/ha spray volume compared with 94 or 190 L/ha. The amount of surfactant in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 14 publications
(23 reference statements)
1
31
0
9
Order By: Relevance
“…Em razão da importância do glifosato para a agricultura mundial, estudos têm sido conduzidos com o objetivo de avaliar a contribuição de diferentes variáveis em sua efi cácia, das quais se podem destacar: dose (Jordan et al, 1997), volume de calda (O'Sullivan et al, 1981;Ramsdale et al, 2003), qualidade da água (Thelen et al, 1995;Ramos & Durigan, 1998;Gauvrit, 2003), estádio fenológico das plantas daninhas (Durigan, 1992;Jordan et al, 1997) e atividade de adjuvantes (O'Sullivan et al, 1981;Pratt et al, 2003;Nurse et al, 2008).…”
Section: Introductionunclassified
“…Em razão da importância do glifosato para a agricultura mundial, estudos têm sido conduzidos com o objetivo de avaliar a contribuição de diferentes variáveis em sua efi cácia, das quais se podem destacar: dose (Jordan et al, 1997), volume de calda (O'Sullivan et al, 1981;Ramsdale et al, 2003), qualidade da água (Thelen et al, 1995;Ramos & Durigan, 1998;Gauvrit, 2003), estádio fenológico das plantas daninhas (Durigan, 1992;Jordan et al, 1997) e atividade de adjuvantes (O'Sullivan et al, 1981;Pratt et al, 2003;Nurse et al, 2008).…”
Section: Introductionunclassified
“…La efectividad del glifosato está influenciada por diversos factores; por ejemplo, numerosos estudios indican que al aplicarlo en volúmenes de agua bajos, se obtienen mejores controles de malezas que cuando el volumen es alto (Jordan 1981; Buhler y Burnside, 1983;Ramsdale et al, 2003;Kogan y Alister, 2008). En un estudio realizado en cámara de crecimiento con cebada, O'Sullivan et al (1981) encontraron que al incrementar los volúmenes de aplicación de 110 a 550 L ha -1 , se redujo la efectividad del glifosato a las dosis de 0.14 y 0.28 kg ha -1 , en comparación con las dosis de 0.56 y 0.84 kg ha -1 .…”
Section: Introductionunclassified
“…The effectiveness of glyphosate is influenced by several factors; for example, numerous studies indicate that when applied in low water volumes, there is a good weed control, than having high volumes (Jordan 1981;Buhler and Burnside, 1983;Ramsdale et al, 2003;Alister and Kogan, 2008). In a study conducted in a growth chamber with barley, O'Sullivan et al (1981) found that increasing the volume of application from 110 to 550 L ha -1 , the effectiveness of glyphosate at rates of 0.14 and 0.28 kg ha -1 was reduced, in comparison to doses of 0.56 and 0.84 kg ha -1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A temática da adição de sulfato de amônio à calda do herbicida glyphosate tem sido estudada intensamente (Salisbury et al, 1991;Thelen et al, 1995;Ramsdale et al, 2003), no entanto somente alguns trabalhos contemplaram espécies com ocorrência no Brasil. Por outro lado, poucos foram os estudos que avaliaram os efeitos da adição de ureia à calda -prática esta comumente utilizada por produtores brasileiros.…”
Section: Introductionunclassified